Pengangkatan Anak Tanpa Penetapan Pengadilan: Tinjauan Hukum Positif dan Hukum Islam (Studi Kasus Desa Balun, Banjarnegara) - Aulia Putri Febyani; Seno Aris Sasmito (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
parenthood. However, adoption without court approval remains prevalent in society, including in Balun Village, Wanayasa Subdistrict, Banjarnegara Regency. This study examines the practice of non-judicial child adoption in the village and analyzes its implications from positive law and Islamic law perspectives, particularly regarding children's rights. Using a qualitative field research approach with data collection through observation, interviews, and documentation, this study identifies three out of six cases of adoption (2020–2025) conducted without court approval. The findings reveal that adoptions in Balun Village are primarily motivated by familial bonds, verbal agreements, and the desire for offspring or improving child welfare. This practice contradicts Government Regulation No. 54 of 2007, leading to legal uncertainty. From a positive law perspective, it violates legal certainty and child protection principles, as the legal status of adopted children remains unclear. Meanwhile, Islamic law, as outlined in MUI Fatwa No. 9 of 1984, permits adoption provided the child’s lineage is preserved, and their identity is maintained. Empirical evidence shows that the community treats adopted children as biological offspring, even registering the adoptive father’s name in official documents—a practice that risks legal and religious complications. The implications include identity ambiguity, inheritance disputes, and potential loss of children’s rights. This study underscores the urgency of legal compliance and public awareness to ensure adoptions align with positive law and Islamic legal principles.